Fatigue Strength Evaluation of Resin-Injected Bolted Connections Using Statistical Analysis - Correia, José António Fonseca de Oliveira (2017)
Different strategies can be used to perform reparations and reinforcements of ancient bolted and riveted metallic bridges. As the riveting process is not currently a common practice, it requires proper equipment and skilled workers. Another solution is the use of welding. However, the weldability of old steels is poor. Bolts are very attractive alternative solutions, and are most commonly used to repair old metallic bridges. Fitted bolts are expensive solutions; the alternative is the use of resin-injected bolts. The behavior of bolted joints with preloaded resin-injected bolts has been studied using quasi-static and creep tests; however, few studies on the slip and fatigue behavior of these joints can be found in the literature. This paper presents an overview of a few experimental programs that were carried out by several authors aiming at evaluating the fatigue behavior of single and double shear resin-injected bolted connections. A comparison between the experimental data of joints with preloaded standard bolts and preloaded resininjected bolts shows a fatigue strength reduction in the latter. Since Eurocode 3 (EC3) suggests the same fatigue strength curve for joints made of resin-injected bolts and standard bolts, this may raise some concerns. Furthermore, research on the feasibility of using both bonded and bolted connections is shown. This last study was performed with high-strength low-alloy structural steel plates and an acrylic structural adhesive for metal bonding. For both case studies, a statistical analysis is performed on fatigue experimental data using linearized boundaries and the Castillo and Fernández-Canteli model. Fatigue design curves are proposed and compared with the design suggestions of several European and North American standards.